The Effect of Premium Income and Investment Returns on the Underwriting of Tabarru Funds in Sharia Insurance Companies in Indonesia for the 2019–2023 Period - Muharomah, Jamilah; Tripuspitorini, Fifi Afiyanti (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study aims to analyze the effect of premium income and investment returns on the underwriting of tabarru funds in sharia life insurance companies in Indonesia during the period 2019–2023. The background of this research is the decline in the growth of sharia insurance assets due to the Covid-19 pandemic which causes an imbalance between increased premium income and decreased investment returns. Data was obtained from the annual financial statements of 15 sharia life insurance companies selected through purposive sampling from 30 companies registered with Sharia Insurance Association (AASI). The method used is panel data regression analysis. The results of the study show that both partially and simultaneously, premium income and investment returns have a positive and significant effect on the underwriting of tabarru funds. This research is expected to support a more optimal management of tabarru funds and in accordance with sharia principles.